Henoch-Schönlein purpura in children: its relation to oral and to oral and oral and dental health - Arlette Suzy Puspa Pertiwi (Dental Journal (Majalah Kedokteran Gigi), 2012)
> Background: Henoch-Schönlein purpura (HSP) is a rare systemic small vessel vasculitis, which commonly occur in childrenbetween 2 and 10 years of age. The course of the disease is often self-limiting, although may manifest long-term renal morbidity. Theseverity of renal involvement decides about the prognosis of this disease. Many factors can trigger the disease attack, which is the mostcommon is bacterial invasion. Since the oral cavity is often refer as infectious foci to other part of the body, it seemed rationally tobe part that contribute the course of disease, thus management of these infectious foci, if possible, gives rise to an astoundingly goodprognosis. Purpose: This paper will describe a review on HSP and the possible association with oral and dental health since it mightbe related to the prognosis of HSP. reviews: Rashes in children are common; they may develop a rash after prescription of antibiotics.Nevertheless there are some childhood diseases that may manifest a rash presentation, such as HSP. It is important for pediatric dentistto have knowledge about HSP and consider the possibility of dental treatment or disease as potential triggers. Conclusion: Oral anddental condition may be the trigger cause of HSP attack. Therefore, it is important for pediatric dental practitioner to be aware of thecourse of the disease in order to limit the expanding complications.> latar belakang: Henoch-Schönlein purpura (HSP) merupakan vaskulitis pembuluh darah kecil sistemik yang jarang terjadi danbiasanya menyerang anak usia 2 hingga 10 tahun. Penyakit tersebut seringkali dapat sembuh sendiri, tetapi pada jangka panjangdapat bermanifestasi dengan morbiditas ginjal. Keparahan keterlibatan ginjal menentukan prognosis penyakit. Banyak faktor yangdapat memicu serangan penyakit, tersering adalah invasi bakteri. Karena rongga mulut sering kali merupakan fokus infeksi terhadapbagian lain dari tubuh, maka mempunyai peluang sebagai faktor pemicu timbulnya penyakit, sehingga penatalaksanaan fokus infeksidalam rongga mulut, jika ada, dapat memberikan prognosis yang baik pada pasien. tujuan: Makalah ini akan menggambarkantinjauan mengenai HSP dan hubungannya dengan kesehatan gigi dan mulut berkaitan pengaruhnya terhadap prognosis HSP. tinjauanPustaka: Ruam sering terjadi pada anak; pasien anak dapat memperlihatkan gejala ruam setelah pemberian antibiotika. Selain itu,beberapa penyakit dapat bermanifestasi sebagai ruam, misalnya HSP. Merupakan hal yang penting bagi dokter gigi anak untuk memilikipengetahuan mengenai HSP dan mempertimbangkan perawatan atau penyakit gigi sebagai pemicu potensial. Kesimpulan: Keadaangigi dan mulut dapat merupakan pencetus serangan HSP, oleh karena itu penting bagi dokter gigi anak untuk memahami perjalananpenyakit sehingga dapat membatasi komplikasi yang terjadi.